Effect of hostplant resistance on growth and developmental parameters of the flower bud thrips, Megalurothrips sjostedti (Trybom) on some resistant cowpea (Vigna unguiculata [L.] Walp.) cultivars - Alabi, O.; Odebiyi, J.; Tamo, Manuele (Elsevier, 2004)
The effect of host plant resistance on growth and developmental parameters of the bean flower thrips Megalurothrips sjostedti Trybom was determined on nine cowpea (Vigna unguiculata L.Walp.) cultivars under laboratory conditions. Newly emerged adults M. sjostedti were confined on peduncles with floral buds of the different cowpea cultivars. M. sjostedti suffered 100% pre-imaginal mortality on cowpea lines Moussa local, TVu1509, TVx3236, Sewe and Sanzibanili. Antibiosis is believed to be the mechanism of resistance operating in these cultivars. On KVx404-8-1, M. sjostedti had a prolonged developmental period though not significantly different from Vita 7, the susceptible check at P<0.01. IT91K-180 supported the development and survival of M. sjostedti with the suitability index (growth index) not significantly different from the susceptible check (Vita 7) at P<0.01. Hence the mechanism of its resistance is tolerance.